2007
DOI: 10.1007/s00531-007-0223-x
|View full text |Cite
|
Sign up to set email alerts
|

Late-Variscan fluid migration at the Variscan thrust front of Eastern Belgium: numerical modelling of the palaeothermal and fluid flow field

Abstract: Modelling of the palaeothermal field at the Variscan thrust front in eastern Belgium indicates significant temperature modifications by late-Variscan palaeofluids migrating from internal to peripheral parts of the orogen. A detailed set of calibration data (chlorite geothermometry, microthermometry, organic rank) gives evidence of temporary palaeotemperature variations at the Variscan thrust front obviously connected to the migration of hot, low saline palaeofluids. These thermal events likely enhanced organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Within the upper Carboniferous of the Wurm syncline vitrinite reflectance increases towards the south and the Aachen thrust (Babinecz 1962;Steingrobe 1990;Teichmüller and Teichmüller 1979;von Winterfeld 1994). Increased organic maturity in this area is explained by enhanced heat flow which was caused by fluid discharge in the footwall of the Aachen thrust (Knapp 1980;Lünenschloss et al 1997Lünenschloss et al , 2008Lünenschloss 1998;Teichmüller and Teichmüller 1979). A similar thermal overprint in the temperature range of 210-310°C can also be assumed for the rock units of the RWTH-1 well.…”
Section: Regional Geology and Fluid Evolutionmentioning
confidence: 96%
See 1 more Smart Citation
“…Within the upper Carboniferous of the Wurm syncline vitrinite reflectance increases towards the south and the Aachen thrust (Babinecz 1962;Steingrobe 1990;Teichmüller and Teichmüller 1979;von Winterfeld 1994). Increased organic maturity in this area is explained by enhanced heat flow which was caused by fluid discharge in the footwall of the Aachen thrust (Knapp 1980;Lünenschloss et al 1997Lünenschloss et al , 2008Lünenschloss 1998;Teichmüller and Teichmüller 1979). A similar thermal overprint in the temperature range of 210-310°C can also be assumed for the rock units of the RWTH-1 well.…”
Section: Regional Geology and Fluid Evolutionmentioning
confidence: 96%
“…Abundant indications of fluid flow are given by high coalification grades in the hanging wall and in the footwall close to the Aachen thrust (Babinecz 1962;Teichmüller and Teichmüller 1979;von Winterfeld 1994) that are interpreted to be the result of Carboniferous and thus Variscan (Knapp 1980) hydrothermal fluid flow. Similarly, Lünenschloss et al (1997Lünenschloss et al ( , 2008 concluded from the regional distribution of vitrinite reflectance that coalification anomalies resulted from significant fluid flow at the Variscan thrust front. Other valuable monitors of fluid flow are mineralised veins that are ubiquitous in many metamorphic settings.…”
Section: Introductionmentioning
confidence: 95%
“…The outcrop along the river consist of the alternating layers of siltstones and low grade metamorphosed sandstones called psammite [51]. During the late Carboniferous, the progressive deformation of Variscan fold-and-thrust belt in Rhenish massif led to an initial burial metamorphism of siltstones and sandstones layers that initiated the upward migration of warm fluids in the northern Variscan front zone driven by Variscan thrusting [52], [53], [54]. These migrated warm fluids are source of the quartz veins.…”
Section: Geological Background a Rursee Areamentioning
confidence: 99%